Model Strategi Pengembangan Sumber Daya Manusia di Desa Wisata Kemiri, Jember, Jawa Timur - Kristiana, Yustisia; Theodosia C. Nathalia (LPSDI Bina Patria, 2024)
The human resource management system that is formed in a tourism village will provide a clear picture of human resources to know their respective roles and duties so that policies in realizing tourism villages can be implemented and minimize the obstacles that occur. This study aims to determine the conceptual framework for human resource development strategies in the Kemiri Tourism Village. Soft System Methodology (SSM) is used to complete these needs. The method used is qualitative. The selected data sources used a purposive sampling method. The data analysis technique used in this study is CATWOE (Customer, Actor, Transformation, Worldview, Owner, Environment) analysis. The results of the study show that the human resource development strategy for Kemiri Tourism Village is a strategic action to create the competence and quality of tourism actors with high competitiveness through various human resource capacity-building programs. Investment in human resources has an important meaning for improving the welfare of the people in the Kemiri Tourism Village